Cyclooxygenase-2 over-expression inhibits liver apoptosis induced by hyperglycemia - Frances, Daniel Eleazar Antonio (2013)
Increased expression of COX-2 has been linked to inflammation and carcinogenesis. Constitutive expression of COX-2 protects hepatocytes from several pro-apoptotic stimuli. Increased hepatic apoptosis has been observed in experimental models of diabetes. Our present aim was to analyze the role of COX-2 as a regulator of apoptosis in diabetic mouse liver. Mice of C57BL/6 strain Wild Type (Wt) and transgenic in COX-2 (hCOX-2 Tg) were separated into Control (vehicle) and SID (Streptozotocin Induced Diabetes, 200mg/kg body weight, i.p.). Seven days post-injection, Wt diabetic animals showed a decrease in PI3K activity and P-Akt levels, an increase of P-JNK, P-p38, pro-apoptotic Bad and Bax, release of cytochrome c and activities of caspases-3 and -9, leading to an increased apoptotic index. This situation was improved in diabetic COX-2 Tg. In addition, SID COX-2 Tg showed increased expression of anti-apoptotic Mcl-1 and XIAP. Pro-apoptotic state in the liver of diabetic animals was improved by over-expression of COX-2. We also analyzed the roles of high glucose-induced apoptosis and hCOX-2 in vitro. Non-transfected and hCOX-2-transfected cells were cultured at 5 mM and 25 mM of glucose by 72 hours. At 25 mM there was an increase in apoptosis in non-transfected cells vs those exposed to 5 mM. This increase was partly prevented in transfected cells at 25 mM. Moreover, the protective effect observed in hCOX-2-transfected cells was suppressed by addition of DFU (COX-2 selective inhibitor), and mimicked by addition of PGE2 in non-tranfected cells. Taken together, these results demonstrate that hyperglycemia-induced hepatic apoptosis is protected by hCOX-2 expression.